DAMPAK LINGKUNGAN PANTI TERHADAP PROSES PENDIDIKAN KARAKTER ANAK ASUH DI PANTI ASUHAN AR-RASYID - Siti Rohmawati; Wardatuz Zahro; Fajar Firmansyah; Ananta Yudhi; Moh. Ibaddurrohman; Januandika Edi Saputra; Adib Sa’dullah; Muhammad Asrori (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Abstract. The orphanage environment has a crucial role in the character education process of foster children. This study analyzes the impact of the physical, social, and coaching programs in the Ar-Rasyid Orphanage on the formation of children's character. Through daily activities, children are taught values such as responsibility, independence, and cooperation. However, there are obstacles such as limited facilities and the number of caregivers that affect the effectiveness of character education. The method used in this study is qualitative, involving observation, interviews, and documentation. The results of the study show that caregivers play an important role model, while social interaction among foster children also supports character formation.